THE IMPORTANCE AND FORMS OF ORGANIZATION OF PRIMARY EDUCATION TEACHERS' USE OF THE PROJECT METHOD IN THE FORMATION OF STUDENTS' LEARNING ACTIVITIES (Academia Science Repository, 2023)
This article is intended for teachers of primary education and provides a broad overview of the use of the project method in teaching mother tongue and reading literacy.